2013
DOI: 10.3389/fpsyg.2013.00400
|View full text |Cite
|
Sign up to set email alerts
|

Temporal oculomotor inhibition of return and spatial facilitation of return in a visual encoding task

Abstract: Oculomotor inhibition of return (O-IOR) is an increase in saccade latency prior to an eye movement to a recently fixated location compared to other locations. It has been proposed that this temporal O-IOR may have spatial consequences, facilitating foraging by inhibiting return to previously attended regions. In order to test this possibility, participants viewed arrays of objects and of words while their eye movements were recorded. Temporal O-IOR was observed, with equivalent effects for object and word arra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 30 publications
(80 reference statements)
6
16
4
Order By: Relevance
“…14 Although IOR is used in models that try to mimic natural viewing behavior, 23,24 recent studies have found evidence against IOR in real-world scenes. 25,26 Rather than an inhibition of the previous fixation location, Smith and Henderson, 27 for example, reported "facilitation of return" during scene viewing. The probability of refixating the last location was greater than or equal to other distancematched locations, providing evidence against the view that IOR drives attention through a scene by decreasing the probability of return.…”
Section: The Role Of Memory In Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…14 Although IOR is used in models that try to mimic natural viewing behavior, 23,24 recent studies have found evidence against IOR in real-world scenes. 25,26 Rather than an inhibition of the previous fixation location, Smith and Henderson, 27 for example, reported "facilitation of return" during scene viewing. The probability of refixating the last location was greater than or equal to other distancematched locations, providing evidence against the view that IOR drives attention through a scene by decreasing the probability of return.…”
Section: The Role Of Memory In Searchmentioning
confidence: 99%
“…Although IOR is used in models that try to mimic natural viewing behavior, recent studies have found evidence against IOR in real‐world scenes . Rather than an inhibition of the previous fixation location, Smith and Henderson, for example, reported “facilitation of return” during scene viewing.…”
Section: The Role Of Memory In Searchmentioning
confidence: 99%
“…Location of Stigchel, & Hollingworth, 2009;Hooge, Over, van Wezel, Maarten, & Frens, 2005;Luke, Schmidt, & Henderson, 2013) concepts. In particular, the difference between fixation duration of regular and the RFs is in agreement with known data (Bays & Husain, 2012;Hooge et al, 2005;Lupianez et al, 2006).…”
Section: Imagesmentioning
confidence: 99%
“…One approach to solving this problem is to study the local elements of the viewing trajectories, in particular, the return gaze fixations on the recently viewed image areas. More and more facts are accumulating about the phenomena of Facilitation of Return [5,[9][10][11][12][13][14][15], but up to now the concept of Inhibition of Return has dominated [7,16]. The oculomotor, endogenous, and exogenous factors that determine the occurrence of the phenomenon of inhibition of return, its spatial and temporal properties are analyzed in detail [7,[10][11][12][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…It is assumed that return-inhibiting mechanisms dominate to solve visual search problems and examine simple images [7,11,20,22]. Instead, the phenomenon of facilitating return often occurs in the visualization of complex images and the resolution of complex visual tasks [9,12].…”
Section: Introductionmentioning
confidence: 99%